A promised land? First summary of the research program - Näsman, Mattias; Bergquist, Ann-Kristin; Björling, Nils; Eriksson, Madeleine; Liliequist, Evelina; Lindmark, Magnus; Lundberg, Johan; Lundgren, Anna-Sofia; Müller, Dieter K.; Rataj, Marcin; Rönnblom, Malin; Scott, David; et al. (Luleå tekniska universitet, Samhällsvetenskap, 2023)
This document lays out the background for the research program “A promised land? Drivers, challenges and opportunities related to the (green) industrialization of Northern Sweden,” (nr. M22-0029) awarded by the Swedish Riksbankens Jubileumsfond’s in 2022. The document summarizes work in progress and may therefore be updated and republished in different versions according to the requirements of the program. This interdisciplinary program aims to understand the economic, social, and political challenges and opportunities of the ongoing industrial transformation in northern Sweden. A key element of the program is to identify drivers, obstacles, and preconditions in a historical, present, and forward-looking processperspective.